Efeitos de análogos da propafenona na reatividade vascular em anéis de aorta isolados de rato Wistar - Lima, Natália Cavalcante Barbosa (2024)
The present study aimed to investigate the effects of propafenone analogs on vascular reactivity using isolated aortic rings from Wistar rats, with the goal of developing new medications for cardiovascular diseases, which are the leading cause of global mortality. The study focuses on four analogs, identified as RAC-5a, RAC-5b, RAC-5c, and RAC-5d, evaluating their potential as vasodilators. The objective was to conduct a screening to assess the effects of these propafenone analogs on vascular reactivity, verifying their vasodilatory effect, and identifying the most promising one based on its potency and efficacy. Additionally, the study aimed to evaluate the affinity of the analogs for β receptors, K+ and Ca2+ channels, in order to subsequently characterize the mechanism of action of the selected analog. The methodology involved the use of adult Wistar rats, whose aortas were isolated and mounted in an organ bath. After a stabilization period, tissue viability tests were performed to ensure the integrity of the smooth muscle and endothelium. The vasodilatory effect was evaluated through dose-response curves with the analogs in aortic rings pre-contracted with phenylephrine (PHE) or KCl, with these experiments being crucial to determine the effectiveness and potential therapeutic use of each analog. In addition to the physiological tests, the study included molecular docking to predict the affinity of the analogs for calcium and potassium channels, as well as proteins related to the nitric oxide pathway, helping to identify the analogs with the highest specificity and potential efficacy, providing a deeper understanding of their interaction with vascular targets. The results showed that the analogs exhibited significant vasodilatory effects, with variations in their potency and efficacy. Among the analogs, RAC-5b stood out as the most promising, demonstrating robust vasodilatory effects in pre-contracted aortic rings, and the molecular docking studies confirmed RAC-5b's high affinity for calcium and potassium channels, suggesting its mechanism of action as a vasodilator. The research concluded that propafenone analogs, especially RAC-5b, have significant potential as vasodilatory agents. These findings suggest that RAC-5b, due to its high efficacy and strong vasodilatory action, could be developed into a new medication for treating cardiovascular diseases, offering a therapeutic alternative with potentially fewer side effects compared to existing treatments. This research opens promising avenues for the development of new cardiovascular treatments based on the structural modification of propafenone, aiming for greater specificity and efficacy of the new compounds. The study emphasizes the need for continued research to better understand the mechanisms of action and potential clinical benefits of these new agents, highlighting the relevance of ongoing drug development to improve cardiovascular disease treatments.